Visible light-conducting polymer nanocomposites as efficient photocatalysts for the treatment of organic pollutants in wastewater - Ahmad, Nafees; Anae, Jerry; Khan, Mohammad Zain; Sabir, Suhail; Yang, Xiao Jin; Thakur, Vijay Kumar; Campo Moreno, Pablo; Coulon, Frederic (Elsevier, 2021)
This review compiles recent advances and challenges on photocatalytic treatment of wastewater using nanoparticles, nanocomposites, and polymer nanocomposites as photocatalyst. The review provides an overview of the fundamental principles of photocatalytic treatment along the recent advances on photocatalytic treatment, especially on the modification strategies and operational conditions to enhance treatment efficiency and removal of recalcitrant organic contaminants. The different types of photocatalysts along the key factors influencing their performance are also critically discussed and recommendations for future research are provided.
Keywords: Band gap; Wastewater treatment; Organic contaminants; Polymer nanocomposites; Photocatalyst